Differences in the relationship between diabetes and prostate cancer among Black and White non-Hispanic men. - Miller, Eric A.; Pinsky, Paul F.; Pierre-Victor, Dudith (Cancer Causes & Control, 2021)
Purpose: Studies finding lower incidence rates of prostate cancer among men with diabetes have been primarily conducted in White non-Hispanic (WNH) populations. The purpose of this analysis is to compare the relationship between diabetes and prostate cancer among Black (BNH) and White non-Hispanic men.Methods: We used Surveillance, Epidemiology, and End Results (SEER)-Medicare data from 2011 to 2015 to compare incidence rates and tumor characteristics between BNH and WNH men by diabetes status. Age-adjusted incidence rates and corresponding rate ratios (RR) by diabetes status were calculated overall and by tumor grade, stage, and PSA level separately for BNH and WNH men. We used multivariable logistic regression to compare tumor characteristics among men with prostate cancer in the numerator, both within and across race/ethnic groups.Results: Overall age-adjusted incidence rates were significantly lower in men with diabetes compared to those without among WNH men [RR = 0.88 95% Confidence Interval (CI) 0.86-0.90] but there was no difference in rates by diabetes status among BNH men (RR = 1.01 95% CI 0.96-1.07). Men with diabetes were less likely to be diagnosed with distant-staged tumors compared to those without diabetes in both race/ethnic groups but the magnitude of difference by diabetes status was greater in BNH [Odds Ratio (OR) = 0.52 95% CI 0.42-0.64] than WNH (OR = 0.88 95% CI 0.81-0.95) men (p-value for interaction < 0.001).Conclusion: The relationship between diabetes and prostate cancer differed between BNH and WNH men. The differences could have implications in evaluating the effectiveness of prostate cancer screening in men with diabetes across racial/ethnic subgroups.